Relocating Aborigines in Sally Morgan’s My Place - Azimullah (University of Chitral Journal of Linguistics and Literature, 2018)
Sally Morgan’s novel My Place explicitly portrays the resistance of Aboriginessubalterns against the prevailing social, economic, cultural and political issues.Focusing on identity, hybridity, ethnicity, and racism, the paper argues howAborigines undergo social injustice, racial distortion, class disparity and adversarialdisplacement by Neo-colonialism. Investigating the Aborigines’ academicendeavours, genealogical suppressive destitutions, groundbreaking reattachment,matrilineal links, it is hypothesized that My Place foregrounds the contemporarystatus of modern Aboriginal Woman. Illustrating the Aborigines’ altruisticpatriotism and excruciating their sufferings during Neo-colonialism in the novel, itis spotlighted how lost generation and stolen generation and extortive afflictionsimposed on the Aborigines by the Whites in Australia have shaped the formers’collective socio-cultural and political consciousness.